Effect of viscosity on the equilibrium scour depth at single cylindrical piers - Lança, Rui (2017)
Most studies on scouring seem to have overlooked the effect of viscosity, the assumption being that the flow is free of viscous effects inside the scour hole because of the presence of highly turbulent flow structures such as down-flow, horseshoe vortex, and wake vortices irrespective of the approach flow regime. The present work reports the results of experiments conceived to revisit the effect of viscosity on scouring. The experiments were performed by changing the Reynolds-like numbers for two flowshallowness values and keeping constant the remaining dimensionless parameters that control the scour process. Thevalues of theReynoldsnumber corresponded to transitional approach flows. The experimental results indicate that scouring does depend on viscosity in usual laboratory conditions, the viscous effect leading to scour depths in the safety side.